2020
DOI: 10.1183/23120541.00288-2019
|View full text |Cite
|
Sign up to set email alerts
|

Low serum free light chain is associated with risk of COPD exacerbation

Abstract: BackgroundMost exacerbations of chronic obstructive pulmonary disease (COPD) are triggered by respiratory tract infections. Adaptive immunity via antibody production is important in preventing infections. Impaired antibody production is reported to be associated with an increased risk of exacerbations of COPD. In the present study, we elucidated whether reduced free light chains (FLCs), which are excessive amounts of light chains produced during antibody synthesis and can be used to estimate systemic antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This suggests that elevated levels of ICs may be related to the decline in lung function in those with COPD. This finding is consistent with other studies and further supports the crucial role of inflammation in the course of COPD (23). These ICs may induce oxidative stress, cell infiltration, and tissue damage, impairing lung function in patients with COPD (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that elevated levels of ICs may be related to the decline in lung function in those with COPD. This finding is consistent with other studies and further supports the crucial role of inflammation in the course of COPD (23). These ICs may induce oxidative stress, cell infiltration, and tissue damage, impairing lung function in patients with COPD (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 92%
“…Comparing COPD patients with various GOLD grades, it was found that the levels of serum FIGLCs and ICs increased gradually with the severity of the disease. This indicates that the levels of serum FIGLCs and ICs are closely related to the severity of COPD and may serve as potential indicators for assessing the condition and predicting the disease progression (23). A study by Tanimura et al investigated the treatment and prognosis of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to a reduction in their concentration, secondary to the increased use during AECOPD episodes, or it may have been the result of a synthesis failure in different immunoglobulins, which in turn could have facilitated the acute episodes. This latter hypothesis appears to be more feasible since various authors have reported low blood levels of free light chains of immunoglobulins in COPD patients, both at AECOPD or even during stable conditions [51][52][53]. In the following paragraphs, the other three protein groups that were associated with the cluster most closely linked to AECOPD will be analyzed in more detail.…”
Section: Main Protein Groups Differentiating Exacerbations From Stabi...mentioning
confidence: 99%
“…High levels of endotrophin and von Willebrand factor as well as other markers of epithelial repair, alveolar destruction, and endothelial dysfunction have been correlated with higher morbidity and mortality in COPD [53 ▪ –56 ▪ ]. Low-serum IgG and free light chain levels have been linked to a higher risk of exacerbation and hospitalization, which suggests a potential role for intravenous immunoglobulin administration in COPD patients with recurrent exacerbations [57 ▪ –59 ▪ ]. High red cell distribution width, a marker of oxidative stress, appears to have excellent accuracy for the identification of the frequent exacerbator phenotype in COPD [60 ▪ ].…”
Section: Biomarkersmentioning
confidence: 99%